The social construction of difference and inequality race, class, gender, and sexuality - Ore, Tracy E. (Boston McGraw-Hill Higher Education, 2008)
Constructing diffences; Maintaining inequalities: Systems of oppression and privilege; Experiencing difference and inequality in everyday life; Resistance and social change.
Includes bibliographical references.
Keywords: Cultural pluralism -- United States; Equality -- United States; Minorities -- Social conditions -- United States; Social classes -- United States; Women; Gays; Discrimination; Hoa Kì (Nước Mĩ); Xã hội học